Evaluation and Characterization of High-Uniformity SiNx Thin Film with Controllable Refractive Index by Home-Made Cat-CVD Based on Orthogonal Experiments - Caifang Li; Minghui Li; Jinsong Shi; Haibin Huang; Zhimei Li (Molecules)
Silicon nitride (SiNx) thin film is a promising coating with great physiochemical and optical properties. However, the preparation of films with good comprehensive properties still faces challenges. This study focused on developing a method for the preparation of uniform SiNx thin film with a controllable refractive index using home-made catalytic chemical vapor deposition (Cat-CVD) equipment. Orthogonal experimental design was employed to investigate the effects of four key influence factors, including reaction pressure, the ratio of SiH4 to NH3, the ratio of SiH4 to H2, and substrate temperature. The response parameters evaluated were the refractive index, extinction coefficient, uniformity, and deposition rate of SiNx thin film. Compared with the single-factor variable tests, an orthogonal experiment could obtain the optimal preparation process of the SiNx thin film with the best comprehensive quality through the least number of experiments. At the same time, the microstructures of SiNx thin film were analyzed by various characterization methods, including Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), to research the relationship between preparation factors and the properties of SiNx thin film. This paper provides the theoretical guidance for fine-regulating the properties of SiNx thin film in practical applications.